DESAIN DIDAKTIS MATERI KAIDAH PENCACAHAN UNTUK SISWA SMA KELAS XI - Muhammad Anang Jatmiko; Tatang Herman; Jarnawi A Dahlan (Universitas Muhammadiyah Lampung, 2021)
This study aims to develop didactic design on counting rules for senior high school. The didactic design is designed by considering two things the result of the test analysis of learning obstacle instrument and learning trajectory. This didactic design consists of four meetings obtained through the three formal stages performed in the study. The first stage is prospective ie didactic situation analysis before learning in the form of hypothetical didactic design including pedagogical didactic anticipation (ADP), second phase metaped analysis is notthe form of design implementation phase, and last stage is retrospective analysis which is an analysis that relate result of prospective analysis with metaped analysis nottik used to formulate empirik design. The research for preparing the didactic design begins with the provision of difficulties in learning the material of the counting rules and the analysis of the teaching materials. The results of the learning obstacle test show that students experience learning barriers that are categorized into three, namely ontogenic obstacle, didactical obstacle, and epistemological obstacle. The didactic design was implemented to 35 students of class XI in one of the senior high school in South Jakarta. Based on the results of research, didactic design developed this can be used as an alternative teaching materials concept of counting rules to minimize student learning barriers.